2013
DOI: 10.1166/jbn.2013.1578
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-Dependent DNA Damage Induced by Gold Nanoparticles

Abstract: The sensitivity of two conformations of plasmid DNA, the A and B forms, to strand break formation induced by gold nanoparticles (GNPs) is investigated by varying the GNP to DNA ratio in solution and the degree of DNA hydration. Decreasing DNA hydration via lyophilisation or by replacement of water with ethanol in solution modifies its conformation from the B to the A form. The yields of single strand breaks (SSB) are found to be highly dependent on the amount of DNA in the A configuration. The damage also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[38][39][40] In recent years, exposure to gold nanoparticles has been reported to cause transient DNA damage due to the generation of alkali-labile sites and oxidative stress with a decrease in glutathione. 41,42 However, the phosphorylation level of H2A.X showed no change after treatment with U2-AuNP 24 hr. We considered that this phenomenon might be caused by a long U2-AuNP treatment time since DNA double-strand breaks (DSBs) happen within several hours.…”
Section: Discussionmentioning
confidence: 94%
“…[38][39][40] In recent years, exposure to gold nanoparticles has been reported to cause transient DNA damage due to the generation of alkali-labile sites and oxidative stress with a decrease in glutathione. 41,42 However, the phosphorylation level of H2A.X showed no change after treatment with U2-AuNP 24 hr. We considered that this phenomenon might be caused by a long U2-AuNP treatment time since DNA double-strand breaks (DSBs) happen within several hours.…”
Section: Discussionmentioning
confidence: 94%
“…Since during transcription the DNA-RNA duplexes adopt the A form, the results of Huang et al further showed that GNP could be genotoxic and that this toxicity could be cell-cycle dependent. 29 In our experiments under UHV conditions, DNA in the GNP complexes is converted to the A form with only structural water left. We therefore interpret our results with no irradiation in terms of the interaction of the GNPs with DNA.…”
Section: Methodsmentioning
confidence: 93%
“…This behavior seems to indicate that electron bombardment simply enhances the process, which causes SSB, when the films of DNA-GNP complexes are dehydrated under UHV. This process has recently been investigated in detail by Huang et al 29 It has been found that in the B form in a water solution, DNA is not sensitive to GNPs, whereas when in the A form, either in vacuum or in solution, contact with GNPs produces SSB. The amount of SSB increases with the number of GNPs bound to DNA.…”
Section: Methodsmentioning
confidence: 99%